Comparison of the prokaryotic and eukaryotic microbial communities in peripheral blood from amyotrophic lateral sclerosis, multiple sclerosis, and control populations. (August 2019) - Ellis, Jeremy E.; Missan, Dara S.; Shabilla, Matthew; Moschonas, Constantine; Saperstein, David; Martinez, Delyn; Becker, Christian V.; Fry, Stephen E.
Abstract: Neurodegenerative diseases are estimated to afflict hundreds of thousands of Americans with vastly more worldwide. The etiologies of amyotrophic lateral sclerosis (ALS) and multiple sclerosis (MS) have yet to be established. Previous studies have suggested an association of these diseases with viruses, bacteria, and eukaryotic microbes, no new therapies have been forthcoming. High-throughput DNA sequencing has enabled the comprehensive analysis of microbial DNA profiles in diseased populations. To date, no amplicon-based next-generation DNA sequencing prokaryotic and eukaryotic community profiling studies have been completed for these diseases. Analysis of peripheral blood samples from control participants as well as ALS and MS participants was used to characterize the hematologic population of microbial DNA. Categorical and multivariate analysis with control for multiple comparisons and aged matched controls revealed differences in microbial DNA contribution in ALS patients compared to others. Notably, sequences that belonging to Ochrophyta were enriched in ALS patient samples. Mechanisms underlying this association, the role of microbial DNA sequences, and the development or progression of ALS may become a fertile subject of inquiry.